Diabetes Mellitus in Patients with Rheumatoid Arthritis: A Systematic Review - Amani Kaawan (AlQalam Journal of Medical and Applied Sciences, 2025)
Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by persistent joint inflammation and systemic manifestations. Diabetes mellitus (DM), particularly type 2 diabetes, is a common metabolic comorbidity among RA patients, influenced by inflammation, medication use, and genetic factors. This systematic review aimed to synthesize evidence on the prevalence, pathophysiological mechanisms, and risk factors linking DM with RA. A comprehensive search was conducted in PubMed, Scopus, Web of Science, and Embase (Jan 2010–Apr 2025) following PRISMA 2020 guidelines. Studies including adult RA patients with confirmed DM or assessing the incidence of DM were included. After screening 467 studies, 22 met the inclusion criteria. The pooled estimate indicated a 1.45-fold increased risk of DM in RA patients, with prevalence ranging from 10% to 24%. Key contributing factors included systemic inflammation, prolonged corticosteroid use, obesity, and physical inactivity. Disease-modifying antirheumatic drugs (DMARDs) such as methotrexate and hydroxychloroquine were associated with improved glucose metabolism. These findings emphasize the bidirectional relationship between RA and DM and highlight the need for early metabolic screening, inflammation control, and therapeutic optimization. Future longitudinal and genetic studies are recommended to clarify causal pathways and preventive strategies.